A dicyanoisophorone-based near-infrared fluorescent probe and its application for detecting thiophenols in water and living cells. (December 2018) - Hong, Jiaxin; Xia, Qingfeng; Feng, Weiyong; Feng, Guoqiang
Abstract: We report herein a new dicyanoisophorone-based colorimetric and near-infrared (NIR) fluorescent probe for rapid detection of thiophenols. This probe possesses a remarkable large Stokes shift (208 nm) and works in almost pure aqueous solution under mild conditions. More importantly, it displays a rapid, highly selective and sensitive dual colorimetric and NIR fluorescent turn-on signal responses for thiophenols and allows the detection of thiophenols in the presence of analytes including amino acids, biothiols and aliphatic thiols. Moreover, the fluorescence of this probe at 655 nm displays a good linear relationship with the thiophenol concentration ranging from 0 to 20 μM, and the detection limit is as low as 12 nM. Furthermore, the practicability of this new probe has been successfully proved by detection of thiophenol in real water samples and bioimaging of thiophenol in living cells. Graphical abstract: Image 1 Highlights: A new colorimetric and NIR fluorescent turn-on probe for thiophenols was reported. This probe shows rapid response, high selectivity and sensitivity for thiophenols. This probe displays a remarkable large Stokes shift (208 nm) and a significant NIR fluorescence enhancement (∼270-fold). This probe can be used to detect thiophenol in both real water samples and living cells.